Sector agroexportador del Perú: Una evaluación de la supervivencia de las micro, pequeñas, medianas y grandes empresas - Pantaleón SantaMarí, Alberto Luis (2024)
The objective of this research was to analyze the dynamics of entry, exit and survival of Peruvian agro-export companies, focusing on how their size affects their performance in international trade. In the quantitative approach study, export data was collected from 2012 to 2023 from the AZATRADE trade intelligence system. The data were processed in SPSS software. The analysis technique was the Kaplan-Meier indicator to evaluate the survival function of the companies. The results revealed a significant variability in the entry and exit of companies in the export market, with a marked increase in the entry of new companies in 2023. In addition, a concentration of the export value was observed in large companies, while micro and small companies, despite being numerous, contributed a smaller percentage of the total exported value. The average survival of companies varied depending on their size, with large companies showing greater longevity. The conclusion shows important factors in the survival of companies such as the scale of operations, financial strength and the solidity of distribution networks. It is recommended to raise new questions related to the relationship of factors and survival, design of government and managerial policies based on the results of the evaluation of the survival of companies according to their size, and experimental intervention programs.